Wetting angles of monovalent indium iodide on different substrates. Issue 1 (31st August 2016) - Cröll, Arne; Markert, Jochen; Volz, Martin; Ostrogorsky, Aleksandar
Abstract : Wetting angles of Indium monoiodide were measured on fused silica and pyrolytic boron nitride (pBN). pBN showed the highest value of 128.5°, vs. 105° for fused silica. The latter showed an extremely strong decrease with temperature. From the wetting angles and the surface tension, the work of adhesion was determined. Unfortunately, a reaction of the pBN with InI precludes its use as a crucible, leaving fused silica as the crucible choice. Abstract : Wetting angles of molten Indium monoiodide (InI) on two different substrates, fused silica and pyrolytic boron nitride (pBN), were measured and compared to literature values for carbon and ceramic aluminum oxide. pBN showed the highest value of 128.5°, versus 105° for fused silica. The latter also showed a strong decrease with temperature, similar to aluminium oxide. From the wetting angles and the known surface tension, the work of adhesion for both substrates was determined. A reaction of the pBN with InI precludes its use as a crucible, however, leaving fused silica as the best crucible choice.